2017
DOI: 10.1007/s00294-017-0685-8
|View full text |Cite
|
Sign up to set email alerts
|

Prions and the concept of polyprionic inheritance

Abstract: Discovery of prions-proteins that are able to convert between structurally distinct states, of which one or more is transmissible, led to the concept of "protein-based inheritance". According to this concept, the formation of prion fibrils causes DNA-independent heritable traits in microorganisms. Recently, we described a new and unusual type of prion inheritance. We showed that the yeast prions [PIN ] and [SWI], like classical genes, demonstrate complementary interaction that causes a phenotypic change in yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Recent advances in the development of a methodology of proteomic screening for amyloids allow to move from identifying individual amyloid proteins to systemic analysis of the prevalence and significance of amyloids in different species 912 . These methods are based on the resistance of amyloid aggregates to treatment with SDS that makes it possible to separate them from most other non-amyloid protein complexes 13 . The amyloid properties of the proteins identified in such screenings should be confirmed by further individual analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in the development of a methodology of proteomic screening for amyloids allow to move from identifying individual amyloid proteins to systemic analysis of the prevalence and significance of amyloids in different species 912 . These methods are based on the resistance of amyloid aggregates to treatment with SDS that makes it possible to separate them from most other non-amyloid protein complexes 13 . The amyloid properties of the proteins identified in such screenings should be confirmed by further individual analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Amyloid fibrils are often found in the extracellular matrix of bacteria, 114 contributing to biofilm formation. It has even been suggested that this (meta) function of amyloids may have arisen many times independently during the evolution of bacteria 115 . Interestingly, some extracellular proteins were also found to form amyloid fibrils in archaea, 116 adding to the universality of this function.…”
Section: Resultsmentioning
confidence: 99%
“…of bacteria. 115 Interestingly, some extracellular proteins were also found to form amyloid fibrils in archaea, 116 adding to the universality of this function.…”
Section: Overlap Of Cellular Component Go Terms Of Prion Candidates A...mentioning
confidence: 99%
“…Recent advances in the development of a methodology of proteomic screening for amyloids allow to move from identifying individual amyloid proteins to systemic analysis of the prevalence and significance of amyloids in different species (12)(13)(14)(15). These methods are based on the resistance of amyloid aggregates to treatment with SDS that makes it possible to separate them from most other nonamyloid protein complexes (16). The amyloid properties of the proteins identified in such screenings should be confirmed by further individual analysis.…”
Section: Introductionmentioning
confidence: 99%